Two decades of ‘Brain Drain’ in Olomouc (Czechia) - Rostislav Netek; Jaroslav Burian; Vit Paszto; Radek Barvír; Jan Chloupek (Journal of Maps, 2022)
This paper and accompanying map aim on the issue of brain drain (otherwise known as Human Capital Flight) concerning cultural and creative industries. The study is focused on the evaluation of Olomouc city, Czechia. In the case of a mid-sized city such as Olomouc, human capital flight is largely associated with cultural and creative fields, because it plays a significant part of the economy and character of the city. The ‘brain drain index’ of Czech municipalities has been calculated and visualized within the synthetic map. The study supported by a map investigated the brain drain from the local university. Moreover, four analytical side-maps which present the most important phenomena used for the Brain Drain Index calculating, and one side-map which summarizes the results of the questionnaire survey, have been visualized. The map layout is extended by description, table and a scheme which characterize the individual steps of the workflow.